2016
DOI: 10.5958/0974-8164.2016.00039.3
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide combinations for control of complex weed flora in transplanted rice

Abstract: A field experiment was conducted to evaluate the bioefficacy of some potent low dose herbicides of sulfonylurea group in conjunction with other traditional recommended herbicides for control of broad spectrum of weeds in transplanted rice (Oryza sativa L) during the wet season of 2012 and 2013. Pretilachlor 750 g/ha as pre-emergence (PE) fb ethoxysulfuron 18.75 kg/ha as post-emergence or pretilachlor 750 g/ha followed by metsulfuron-methyl + chlorimuron-ethyl 4 g/ha or pyrazosulfuron 20 g/ ha (PE) followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
8
4
0
Order By: Relevance
“…This is simply due to higher grain and straw yield of the crop obtained from these treatments. Similar result was reported by Yakadri et al, (2016). Though the rice yield and gross return were the highest under hand weeding at 15, 30 and 45 DAS, the data on net income and return per rupee invested showed that it was less remunerative than pendimethalin at 1.0 kg ha -1 at 2 DAS + bispyribac sodium at 25 g ha -1 at 20 DAS and pendimethalin at 1.0 kg ha -1 + one manual weeding at 30 DAS which implied that it was uneconomic and unnecessary to give three hand weeding during the entire crop growth.The net income was found negative under weedy check due to greater competition between rice and weed which led to poor growth of the crop, lower grain and straw yield.…”
Section: Effect On the Performance Of Rice Cropssupporting
confidence: 92%
“…This is simply due to higher grain and straw yield of the crop obtained from these treatments. Similar result was reported by Yakadri et al, (2016). Though the rice yield and gross return were the highest under hand weeding at 15, 30 and 45 DAS, the data on net income and return per rupee invested showed that it was less remunerative than pendimethalin at 1.0 kg ha -1 at 2 DAS + bispyribac sodium at 25 g ha -1 at 20 DAS and pendimethalin at 1.0 kg ha -1 + one manual weeding at 30 DAS which implied that it was uneconomic and unnecessary to give three hand weeding during the entire crop growth.The net income was found negative under weedy check due to greater competition between rice and weed which led to poor growth of the crop, lower grain and straw yield.…”
Section: Effect On the Performance Of Rice Cropssupporting
confidence: 92%
“…This is simply due to higher grain and straw yield of the crop obtained from these treatments and comparatively lower cost involved in the cultivation of crop under these treatments. Similar result was reported by Yakadri et al (2016). Though the rice yield and gross return were the highest under hand weeding at 15, 30 and 45 DAS, the data on net income and return per rupee invested showed that it was less remunerative than pendimethalin at 1.0 kg/ ha at 2 DAS + bispyribac-sodium at 25 g/ha at 20 DAS and pendimethalin at 1.0 kg/ha + one manual weeding at 30 DAS, which implied that it was uneconomic and unnecessary to give three hand weeding during the entire crop growth.…”
Section: Economicssupporting
confidence: 92%
“…The results implied that controlling weeds on rice field twice or more will efficiently reduce weeds population and dry weight, leading to better nutrient, moisture and light uptake by crops. This is in agreement with Yakadri et al (2016) who reported that the application of herbicides alongside with manual weeding produced lesser weed dry matter accumulation than the weedy check. The increased weed biomass in no weeding treatment may be attributed to the fact that the weeds were not managed, which contributed to their growth and translated into increased biomass.…”
Section: Weed Biomass and Weed Control Efficiencysupporting
confidence: 93%
“…The maintenance of weed free conditions in rice fields is crucial to enhance grain yields. The results conform to other research where higher grain yield was found in weed free checks (Singh et al, 2018;Dzomeku et al, 2017;Yakadri et al, 2016;Hakim et al, 2013). The greater grain yield recorded by MF compared to CD and PL, though they were all applied at 60 kg N ha -1 which may be attributed to slow release of organic nutrients (CD and PL) compared to MF (Senayah, 2009).…”
Section: Grain Yieldsupporting
confidence: 92%